LEXICAL AMBIGUITY AS A SOURCE OF HUMOUR: THE CASE OF MEMES ON INSTAGRAM - Haryadi, Didan; Rejeki, Sari; Setyowati, Agnes (Journal Albion : Journal of English Literature, Language, and Culture, 2022)
This study is conducted to analyze lexical ambiguity in memes on Instagram. The method used in this study is qualitative-descriptive. 21 memes that were collected from August 2020 August 2021 utilize ambiguous words. The results of the analysis show that lexical ambiguity can be applied as an element to add humor to memes. By taking advantage of incongruity theory, words that have multiple meanings are employed to create misunderstandings or mistakes that make the memes humorous.Keywords: lexical ambiguity; memes; humor.